Diseño de un programa de mantenimiento para mejorar la confiabilidad de los equipos de la empresa BUZCA S.A (2023)
This research highlights the importance of maintenance in organizations for the preservation of their assets, and the influence that the process has on the finances of a company, from the point of view that when there are unforeseen failures in the equipment, it is necessary to carry out an unforeseen investment, which represents operational cost overruns.